Platessa congqiancuoensis sp. nov., a new freshwater diatom species (Bacillariophyceae) from a mountain lake, Sichuan Province, China, and a new morphology within the catch-all genus Platessa - Zhang, Wei; Zheng, Yaqi; Yin, Sicheng; Kociolek, John Patrick; Wang, Ni (Phytotaxa, 2025)
Platessa congqiancuoensis sp. nov., a new freshwater diatom from Lake Congqiancuo (Sichuan, China), is described using light and scanning electron microscopy. Diagnostic features include an elliptical-lanceolate valve outline, narrowly linear axial area, and a rhombic to oval central area bordered by 4–5 shortened striae. Striae transition radially from the valve center to convergent apices, with hooked terminal raphe ends deflected in opposite directions. The species is distinguished from morphologically similar taxa (P. mugecuoensis, P. stewartii, P. bahlsii, and P. brevicostata) by valve dimensions, shape, striae density, and ultrastructural details. We further contextualize Platessa within related genera and discuss potential taxonomic linkages.